Gaokao i procesy stratyfikacji społecznej w Chinach - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2017)
This article concerns „gaokao” Chinese exams. I show how the „high stakes” tests (the essence of these exams) create the winners and losers in the battle for stratification success. They set up, as a one-time „selection act”, the trajectory of a career and the whole future life of young Chinese. At the same time, they are an example of the entanglement of the testing process in politics and of the enormous (and overwhelming) social pressure on young people.
Gaokao and Processes of Social Stratification in China
Keywords: gaokao; high-stakes test; stratification; socialization